ULTRASOUND IN THE ENDODONTIC: POSSIBILITY AND PROSPECTS - Udod, A.A.; Fomina, T.V. (World of Medicine and Biology, 2013)
In a review article modern possibilityes have been analyzed for endodontic treatment. Physical basics, principles of ultrasound devices acting, stages of development and implementation of ultrasound technology in the practice of endodontic are described. Prospects of further ultrasound are presented in general clinical practice.